2010
DOI: 10.1517/17425241003602259
|View full text |Cite
|
Sign up to set email alerts
|

Drug release kinetics and transport mechanisms of non-degradable and degradable polymeric delivery systems

Abstract: Importance of the field-The advancement in material design and engineering has led to the rapid development of novel materials with increasing complexity and functions. Both non-degradable and degradable polymers have found wide applications in the controlled delivery field. Studies on drug release kinetics provide important information into the function of material systems. To elucidate the detailed transport mechanism and the structure-function relationship of a material system, it is critical to bridge the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
602
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,000 publications
(654 citation statements)
references
References 91 publications
16
602
1
Order By: Relevance
“…According to the present data, this molecule loaded into NC may also be useful in controlling the exacerbated immune response in the periodontal tissues under pathogen challenge. The observed slow release rate of 15d-PGJ 2 could be related to its interactions with the oily core or the polymeric matrix of the NC (27) and suggested that the drug release mechanism was governed by Fickian diffusion (28). This gradual release of the 15d-PGJ 2 from the NC may be important in determining its pharmacological activity, as observed previously by Alves et al (16).…”
Section: Discussionsupporting
confidence: 63%
“…According to the present data, this molecule loaded into NC may also be useful in controlling the exacerbated immune response in the periodontal tissues under pathogen challenge. The observed slow release rate of 15d-PGJ 2 could be related to its interactions with the oily core or the polymeric matrix of the NC (27) and suggested that the drug release mechanism was governed by Fickian diffusion (28). This gradual release of the 15d-PGJ 2 from the NC may be important in determining its pharmacological activity, as observed previously by Alves et al (16).…”
Section: Discussionsupporting
confidence: 63%
“…This variation presents a caveat in the use of control Ags, such as lysozyme, that result in more neutrally charged particles. Additionally, different Ags would be expected to have distinct release kinetics from PLG(Ag) in solution, with factors such as Ag size, charge, and hydrophobicity affecting the release rate (19). Differential binding of OVA-IgE and OVA-IgG1 to the surface of OVA-PLG vs. PLG(OVA) may explain the differences in postsensitization efficacy between OVA-PLG and PLG(OVA) (i.e., binding of OVA-specific Abs to OVA-PLG may target particles to nontolerogenic uptake pathways).…”
Section: Discussionmentioning
confidence: 99%
“…[139] Lastly, solvent penetration/system swelling caused by water penetration into the polymer matrix also contributes to the drug release. [140] The drug release profile from PLGA-based DDSs is a biphasic curve, with an initial burst followed by a sustained release. [88a] This burst release is considered the major problem in DDSs development since they are characterized by a controlled release profile.…”
Section: Drug Release From Poly(lactic-co-glycolic) Acid Delivery Sysmentioning
confidence: 99%